SBA-15-oxynitrides as a solid-base catalyst: effect of nitridation temperature on catalytic activity - Singh, Baljeet; Mote, Kaustubh R.; Gopinath, Chinnakonda S.; Madhu, Perunthiruthy K.; Polshettiwar, Vivek (Angewandte Chemie-International Edition, 2015)
Solid bases, such as SBA-15-oxynitrides, have attracted considerable interest for potential applications as catalysts in important industrial processes. Reported herein is that by simply tuning the temperature of nitridation (ammonolysis), the catalytic activity of these solid bases can be enhanced. Solid-state NMR spectroscopy and XPS studies provided the reasoning behind this change in activity.
Keywords: heterogeneous catalysis; Nanostructures; NMR spectroscopy; photoelectron spectroscopy; solid-state structures

Photoactive anthraquinone-based host-guest assembly for long-lived charge separation - Jha, Ajay; Mote, Kaustubh R.; Chandra, Suman; Madhu, Perunthiruthy K.; Dasgupta, Jyotishman (Journal of Physical Chemistry C, 2021)
Porous 2D covalent organic frameworks (COF) that are assembled axially through weak p-stacking interactions can provide reticular charge transport channels while playing host to kinetically stabilized reactive molecular redox states. Here we demonstrate a host-guest supramolecular charge transfer (CT) assembly using photoactive anthraquinone-based COF as an acceptor while incarcerating the electron donor N,N-dimethylaniline (DMA) inside it. Employing femtosecond broadband transient absorption spectroscopy in combination with electron paramagnetic resonance (EPR) studies, we show that the CT occurs rapidly within <110 fs after photoexcitation, subsequently leading to long-lived charge separation with 13% quantum efficiency at room temperature. The photoinduced EPR signature of the long-lived confined DMA cation radical confirms the disparate regions of charge localization while H-1-C-13 correlation experiments using solid-state NMR spectroscopy enumerate the packing of the amines inside the host-guest COF assembly. Our work demonstrates the potency of charge transport pathways in supramolecular assemblies for efficient charge separation which if optimally tuned should pave the way for COF-based photocatalytic reaction centers.